Research Status and the Prospect of Fractal Characteristics of Soil Microstructures - Jiandong Li; Shengjie Jia; Xu Wang; Yanjie Zhang; Deren Liu (Fractal and Fractional)
The fractal characteristics of soil microstructures, including the size, distribution, and dynamic evolution process of soil particles, cracks, and intergranular pores, are important factors influencing the macroscopic physical properties of soils. Quantitative characterization, qualitative analysis, and the impact of fractal characteristics on macroscopic properties have been important research directions in recent years. This paper summarizes the research status on soil microstructure fractal characteristics, elaborating on the kinds of soil fractal characteristics, the calculation methods of fractal characteristic parameters, and the influence of fractal characteristics on macroscopic properties. Based on existing research results, this paper proposes that future research on soil microstructure fractal characteristics should focus on the following aspects: (1) advancing fractal characteristic research towards higher precision and multi-dimensionality to reveal the internal relations between soil fractal characteristics and macroscopic physical properties; (2) strengthening interdisciplinary collaboration to promote theoretical innovation in fractal analysis and build a more comprehensive system for studying the evolution of soil fractal characteristics; and (3) a close integration with engineering tests to promote the application and transformation of research results, providing valuable references for optimizing construction schemes and improving the service performance of engineering structures.